Development of kartogenin-conjugated chitosan–hyaluronic acid hydrogel for nucleus pulposus regeneration. (6th March 2017) - Zhu, Yanxia; Tan, Jie; Zhu, Hongxia; Lin, Guangyao; Yin, Fei; Wang, Liang; Song, Kedong; Wang, Yiwei; Zhou, Guangqian; Yi, Weihong
Abstract : Injectable constructs for in vivo gelation have many advantages in the regeneration of degenerated nucleus pulposus. Abstract : Injectable constructs for in vivo gelation have many advantages in the regeneration of degenerated nucleus pulposus. In this study, an injectable hydrogel consisting of chitosan (CS) and hyaluronic acid (HA) crosslinked with glycerol phosphate (GP) at different proportions (CS : GP : HA, 6 : 3 : 1, 5 : 3 : 2, 4 : 3 : 3, 3 : 3 : 4, 2 : 3 : 5, 1 : 3 : 6, V : V : V) was developed and employed as a delivery system for kartogenin (KGN), a biocompound that can activate chondrocytes. In vitro gelation time, morphologies, swelling, weight loss, compressive modulus and cumulative release of KGN in hydrogels were studied. For biocompatibility assessments, human adipose-derived stem cells (ADSCs) were encapsulated in these hydrogels. The effects of KGN on stem cell proliferation and differentiation into nucleus pulposus-like cells were examined. The hydrogels with higher concentrations of HA showed a slightly shorter gelation time, higher water uptake, faster weight loss and faster KGN release compared to the hydrogels with lower concentrations of HA. As the KGN-conjugated hydrogel prepared with the proportions 5 : 3 : 2 displayed good mechanical properties, it was chosen as the optimal gel to promote cell proliferation and differentiation. No significant difference was seen in the expression levels of nucleus pulposus markers induced by KGN or TGF-β. Additionally, inclusion of KGN and TGF-β together did not produce a synergistic effect in inducing nucleus pulposus properties. In conclusion, we have developed a KGN-conjugated CS/HA hydrogel (5 : 3 : 2) with sustained release of KGN in hydrogel that can promote ADSC proliferation and nucleus pulposus differentiation. This kind of hydrogel may be a simple and effective candidate for the repair of degenerative NP tissue after minimally invasive surgery.